ANALYSIS OF VALUE ADDED TAX CALCULATION AT PT. ROGANDA GRACIA ARTHA - Rifki Nandar Febriyan; Junawan; Nancy Mayriski Siregar (RADJA PUBLIKA, 2025)
This study aims to analyze the calculation and reporting of Value Added Tax (VAT) at PT. Roganda Gracia Artha, a service and trading company in Medan City that has been confirmed as a Taxable Entrepreneur (PKP). VAT is an indirect tax that has a large contribution to state revenue, so its management must be carried out appropriately in accordance with statutory provisions, especially Law No. 42 of 2009. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation of the company's finance and taxation departments. This study was conducted to determine the extent of the company's accuracy and compliance in calculating, collecting, depositing, and reporting VAT during the 2024 tax year. The results of the study indicate that PT. Roganda Gracia Artha experiences problems in reporting and recording VAT, such as overpayments almost every month, inconsistencies in reporting times with the actual tax period, and a lack of staff understanding of the tax invoice mechanism and e-SPT reporting. This has implications for potential losses and administrative sanctions from the tax authorities. Therefore, it is necessary to improve the internal control system, human resource training, and more optimal use of information technology to ensure that the implementation of tax obligations is more effective and in accordance with applicable regulations.